Building programme theory to develop more adaptable and scalable complex interventions: Realist formative process evaluation prior to full trial. (April 2019) - Brand, Sarah Louise; Quinn, Cath; Pearson, Mark; Lennox, Charlotte; Owens, Christabel; Kirkpatrick, Tim; Callaghan, Lynne; Stirzaker, Alex; Michie, Susan; Maguire, Mike; Shaw, Jennifer; Byng, Richard
Medical Research Council guidelines recognise the need to optimise complex interventions prior to full trial through greater understanding of underlying theory and formative process evaluation, yet there are few examples. A realist approach to formative process evaluation makes a unique contribution through a focus on theory formalisation and abstraction. The success of an intervention is dependent on the extent to which it gels or jars with existing provision and can be successfully transferred to new contexts. Interventions with underlying programme theory about how they work, for whom, and under which circumstances will be better able to adapt to work with (rather than against) different services, individuals, and settings. In this methodological article, we describe and illustrate how a realist approach to formative process evaluation develops contextualised intervention theory that can underpin more adaptable and scalable interventions. We discuss challenges and benefits of this approach.